Indonesian Language Training Management on Teacher Competency, Profession, and Social Affairs - Tarigan, Budi Akhmad; Komari (Universitas Pendidikan Ganesha, 2024)
Observation results showed that 42% of language teachers were satisfactory and 52% were unsatisfactory. Student achievement and exam results in Indonesian language lessons dropped drastically in 2016. Another fact is that of the 31,464 teachers, 83.89% were at the expected, satisfactory, weak, and very weak levels. This condition is urgent to research. The aim is to analyze the impact of competency management training on the knowledge and understanding of Indonesians, personally, professionally, and socially. Research method use in this study is descriptive survey. The population was selected using purposive sampling involving 210 out of 380 teachers from education throughout Indonesia. Data collection techniques is using questionnaires as the instrument. Statements in the questionnaire are constructed based on 2 standards, namely Knowledge and Understanding. Questions are asked to be rated on a 1-5 point Likert Scale. Instruments were distributed to human resources, namely teachers via Google. Analysis techniques with data statistics show percentages, standard deviations, and average scores, as well as describe relationships based on Pearson correlation statistics. The results show that the average knowledge and understanding score is (M = 4.51, SD = 0.39) among language teachers quite high. There is a relationship between the three domains (r = 0.178). The data also proves that there is a significant relationship between knowledge management training and understanding Indonesian with competence in three domains, namely personal, professional, and social domains.